2019
DOI: 10.3389/fendo.2019.00173
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Affects Musculoskeletal Development and Muscle Lipid Metabolism of Gilthead Sea Bream (Sparus aurata)

Abstract: World population is expected to increase to approximately 9 thousand million people by 2050 with a consequent food security decline. Besides, climate change is a major challenge that humanity is facing, with a predicted rise in mean sea surface temperature of more than 2°C during this century. This study aims to determine whether a rearing temperature of 19, 24, or 28°C may influence musculoskeletal development and muscle lipid metabolism in gilthead sea bream juveniles. The expression of growth hormone (GH)/i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 68 publications
3
17
0
Order By: Relevance
“…On the other hand, igf-2 and gh receptors (ghr-1 and ghr-2) remained unaltered or increased in the case of ghr-2 in bone, supporting the recognized major involvement of IGF-1, compared to the other components of the hormonal axis such as GH, directly controlling musculoskeletal growth in fish [29][30][31]. This GH-IGFs axis gene expression pattern is in agreement with that previously described in a shorter trial (i.e., 3 days) with the same species reared as well at 28 • C temperature [26]. In addition, the up-regulating effect of high temperature on ghr-2 observed in this study in bone was also reported in the liver of rainbow trout (Oncorhynchus mykiss) juveniles [32] and embryos of the same species [33].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…On the other hand, igf-2 and gh receptors (ghr-1 and ghr-2) remained unaltered or increased in the case of ghr-2 in bone, supporting the recognized major involvement of IGF-1, compared to the other components of the hormonal axis such as GH, directly controlling musculoskeletal growth in fish [29][30][31]. This GH-IGFs axis gene expression pattern is in agreement with that previously described in a shorter trial (i.e., 3 days) with the same species reared as well at 28 • C temperature [26]. In addition, the up-regulating effect of high temperature on ghr-2 observed in this study in bone was also reported in the liver of rainbow trout (Oncorhynchus mykiss) juveniles [32] and embryos of the same species [33].…”
Section: Discussionsupporting
confidence: 88%
“…In fact, it is known that the two isoforms of the GH receptor are differentially regulated depending on the tissue, in response to a temperature change [32], which agrees with the results observed in the present work. Furthermore, an increase (not significant) of igfbp-1a, an important growth and development inhibitor [34], was also observed in both tissues in agreement with Balbuena-Pecino et al [26]. All in all, the transcriptional modulation of GH-IGFs axis members in gilthead sea bream caused by the elevation of water rearing temperature to 28 • C appears to be contributing to a critical turnover regulation of the musculoskeletal system to find growth homeostasis.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…While analyzing the probabilities we focused on two thermal limits. Based on literature the upper and lower limits of SWT were considered as 26 • C and 15 • C (Mayer et al, 2008;Ibarz et al, 2010;Llorente and Luna, 2013;Balbuena-Pecino et al, 2019). Various studies specify varying thresholds for seabream.…”
Section: Deterministic Verification Measuresmentioning
confidence: 99%
“…For operational decision making in aquaculture farms, temperature is an important environmental property (Hurst, 2007;Ibarz et al, 2010;Besson et al, 2016;Masroor et al, 2018). Fish species have tolerance levels of temperature and beyond these tolerance levels, fish growth and health are adversely impacted (Berlinsky et al, 2007;Llorente and Luna, 2013;Balbuena-Pecino et al, 2019). At such scenarios, to run the farm business profitably, appropriate measure needs to be taken related to operations (Besson et al, 2016;Hobday et al, 2016).…”
Section: Introductionmentioning
confidence: 99%